2019
DOI: 10.3390/f10090799
|View full text |Cite
|
Sign up to set email alerts
|

Bark Features for Identifying Resonance Spruce Standing Timber

Abstract: Measuring the acoustic properties of wood is not feasible for most luthiers, so identifying simple, valid criteria for diagnosis remains an exciting challenge when selecting materials for manufacturing musical instruments. This article aims to verify whether the bark qualities as a marker of resonance wood are indeed useful. The morphometric and colour traits (in CIELab space) of the bark scales were compared with the structural (width and regularity of the growth rings and of the latewood) and acoustic featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…The database, originally in.txt format, was imported/converted and primarily processed in Microsoft Excel. The digital format of the growth rings consists of the total ring width (TRW), the early wood width (EWW), the late wood width (LWW), the early wood proportion (EWP), and the late wood proportion (LWP) from TRW [16][17][18][19][20]. Regarding the anatomical features of spruce wood-it is known that this species is characterized by distinct areas of early wood formed in the vegetative period and late wood, formed in the period of vegetative rest, being composed of tracheid, rays, and resin channels.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The database, originally in.txt format, was imported/converted and primarily processed in Microsoft Excel. The digital format of the growth rings consists of the total ring width (TRW), the early wood width (EWW), the late wood width (LWW), the early wood proportion (EWP), and the late wood proportion (LWP) from TRW [16][17][18][19][20]. Regarding the anatomical features of spruce wood-it is known that this species is characterized by distinct areas of early wood formed in the vegetative period and late wood, formed in the period of vegetative rest, being composed of tracheid, rays, and resin channels.…”
Section: Methodsmentioning
confidence: 99%
“…Some have opined that the vibrational properties of wood are determined on the scale of the cell wall rather than on the macroscopic scale of the growth rings [12][13][14]. In the stringed instruments industry, musical instruments are classified according to the anatomical quality of the wood used in their construction, with this aspect being revealed in the final price of the instrument [15][16][17]. The classification of quality raw materials for the manufacture of stringed instruments is discussed in detail elsewhere [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of the anatomical features of the wood in the construction of the top and back plates of old violins was performed using a WinDENDRO Density image analysis system (Régent Instruments Inc., Québec City, QC, Canada, 2007) from the Department of Forest Engineering, Forest Management Planning and Terrestrial Measurements, Transilvania University of Bras , ov, Romania (Figure 4a,b). The characteristics of the annual rings were measured in terms of the width of the annual rings denoted TRW, the width of the early wood EWW, the width of the late wood LWW and the wavelength of the curly fiber of maple (wavelength CWL) according to the method presented in previous studies [23][24][25]. The annual rings were measured in two or three directions, depending on the objective local difficulties in identifying the contour of the rings, especially for old violins, starting from the edge of the sides to the welding line of the face halves (Figure 4a,b).…”
Section: Wood Structure Data Acquisitionmentioning
confidence: 99%
“…Dinulică et al [14] measured the acoustic properties of wood for identifying simple, valid criteria for diagnosis, which remains an exciting challenge when selecting materials for manufacturing musical instruments. The results showed that the spruce trees with acoustic and structural features that match the requirements for the manufacture of violins have a bark phenotype distinguishable by color-as well as by scale shape.…”
mentioning
confidence: 99%